Ethmocephaly: a rare but lethal congenital anomaly - Chaudhary, Aneeta; Arya, Arun Kumar (International Journal of Contemporary Pediatrics, 2024)
Ethmocephaly is a rare but lethal congenital anomaly. Its incidence rate is 1 in 15,000 live births and 1 in 250 in abortuses. Babies have typical dysmorphic facies in form of orbital hypotelorism, proboscis and low set malformed ears. 32 years old, daily wage labourer delivered a baby with ethmocephaly. Baby had typical facies, and no extracranial abnormality present. Baby was stillborn. She had no antenatal checkup or ultrasonogram done. However, she had history of ingestion of certain plants during early months of pregnancy. Ethmocephaly is a lethal anomaly and mostly eliminated prenatally. Although there is no diagnostic test for ethmocephaly, and confirmation of it is done only by appearance of baby after birth, important clues like recognition of risk factors like maternal diabetes, alcohol intake, ingestion of certain plants, antenatal hydrocephalus, should not be missed. Importance of routine antenatal checkup and ultrasonogram is emphasized. Recognition of risk factors and a possible co-relation with ingestion of certain other plants is also emphasized.